The risks of being a preterm twin - Ceran, Burak; Cakir, Ufuk; Tugcu, Ali Ulas; Tayman, Cuneyt (Annals of Medical Research, 2022)
Aim: Twins may have additional clinical problems compared to singletons, but there is insufficient information about whether preterm twins (especially those born before 32 weeks of gestation) are at greater risk than singletons. This study aimed to compare morbidity and mortality in twins and singletons born before 32 weeks of gestation. Materials and Methods: Infants whose gestational age (GA) ≤ 32 weeks were followed in our unit between July 2019 and December 2020 were examined retrospectively. The clinical and demographic characteristics of the infants were recorded and compared between twins and singletons.Results: 770 preterm infants were included in the study, 584 singletons and 186 twins. The singleton group had higher rates of maternal hypertension and small for GA status, while the rate of cesarean delivery was higher in the twins group (p
Keywords: Twin; singleton; preterm; morbidity; mortality